Nrf2-Heme oxygenase-1 modulates autophagy and inhibits apoptosis triggered by elevated glucose levels in renal tubule cells - Joo-Heon Kim; Kyeong Min Kim; Jin Uk Jeong; Jong Ho Shin; Jae Min Shin; Ki Tae Bang (Kidney Research and Clinical Practice, 2019)
Background : Autophagy is a highly balanced process in which lysosomes remove aged and damaged organelles and cellular proteins. Autophagy is essential to maintain homeostasis in the kidneys.